Extraction of keratinase enzyme from marine Actinomycetes and its antibacterial againts S.aureus : Ekstraksi enzim keratinase dari Actinomycetes laut dan potensi antibakterinya terhadap S.aureus - Rieuwpassa, Irene Edith; Khatimah, Amraida Khusnul; Gunawan, Muh. Chaerul; Maulana, Lalu Novan; Makkawaru, Fadhlan Isnan; Sa, Salsabyila Wahyuni; Amin., Zalzabila M. (Makassar Dental Journal, 2025)
Staphylococcus aureus is an important pathogen often associated with serious infections and antibiotic resistance. In the search for alternative treatments, marine Actinomycetes are a potential source due to their ability to produce bioactive enzymes, one of which is keratinase. In addition to its function in keratin degradation, this enzyme is also known to have potential as an antibacte-rial agent. This article explores the extraction of keratinase enzymes from marine Actinomycetes isolates and tests their antibac-terial activity against S.aureus, as a first step in the utilisation of marine biotechnology for medical and pharmaceutical purposes. This systematic review was compiled based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Initial search results of 135 articles were then excluded, yielding four articles that showed that marine Ac-tinomycetes have antibacterial potential against S.aureus. It was concluded that the extraction of keratinase enzymes from ma-rine Actinomycetes showed significant antibacterial activity against S.aureus, indicating the potential of keratinase as an alter-native agent for treating gram-positive bacterial infections, especially amid increasing resistance to antibiotics.